2021
DOI: 10.1139/cjc-2020-0506
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory activities to support online chemistry courses: a literature review

Abstract: The laboratory is an essential element in the teaching and learning of chemistry, but it is challenging to provide this when delivering courses and programs online or at a distance. Studies have repeatedly shown that alternate laboratory modes can lead to equivalent student performance when compared with in-person experiences. In this literature review, we will examine five modes of laboratory delivery (i.e. face-to-face, virtual, remote control, home-study kits and, to a lesser extent self-guided field trips)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…Distance learning and experimenting at home have inevitably gained importance in the recent years due to the COVID-19 pandemic and the subsequent campus and school closures. (Domenici, 2020;Kennepohl, 2021;Schultz et al, 2020). It can be challenging to design suitable home experiments with easily accessible and safe materials, which means that experiments sometimes have to be adapted and simplified for home use.…”
Section: / 12mentioning
confidence: 99%
“…Distance learning and experimenting at home have inevitably gained importance in the recent years due to the COVID-19 pandemic and the subsequent campus and school closures. (Domenici, 2020;Kennepohl, 2021;Schultz et al, 2020). It can be challenging to design suitable home experiments with easily accessible and safe materials, which means that experiments sometimes have to be adapted and simplified for home use.…”
Section: / 12mentioning
confidence: 99%
“…To address this issue, teachers started to employ laboratory activities to teach redox reactions either by performing demonstrations or by having students conduct experiments. Laboratory experiences are an integral part of chemistry instruction, providing students the opportunity of experiencing the macroscopic nature of redox reactions [10], examples of which include reactions between steel wool and copper sulfate, copper (II) and zinc [11,12], and iron nail with copper sulfate and zinc sulfate [8]. These lab experiences provide students the opportunity of observing some sort of phenomena with their naked eyes, such as the color change of a solution or the formation of a new metal.…”
Section: Introductionmentioning
confidence: 99%
“…The American Chemical Society, for instance, requires 400 h of laboratory experience beyond the introductory chemistry laboratory for its accredited bachelor’s degree programs and explicitly states that virtual laboratory experiences do not count toward these hours . However, traditional hands-on laboratory experiences are not always possible or practical due to school closures, financial concerns, or safety issues; thus, educators have sought out alternative methods of laboratory instruction. …”
mentioning
confidence: 99%
“…While virtual laboratory experiences cannot fully replicate traditional laboratory instruction, many studies have reported positive outcomes associated with these digital laboratory courses . Laboratory simulations are useful for introducing new concepts to students who are less familiar with laboratory work, because the cognitive load associated with simulations is smaller than the corresponding in-person experiments . They can also allow students to visualize and manipulate variables that would not be observable in a physical laboratory, which can help students make connections between different representations with varying levels of abstraction .…”
mentioning
confidence: 99%
See 1 more Smart Citation